Analisis Determinan Kebahagiaan Subjektif Wanita Pekerja - Harmen, Salsabila Yori; Alden, Kevin Noelee Dieter; Ervani, Eva (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Various factors such as marital status, age, education level, health condition, and other determinants have an impact on subjective happiness. This study investigates what factors influence subjective happiness among Indonesian female workers based on the fifth wave of Indonesian Family Life Survey data collected in 2014. The study analysis used the probit method. The analysis shows that divorced female workers show a significantly reduced likelihood of happiness compared to married women with statistical significance at p-value < 0.01. Female workers who have completed a higher level of education and maintain better physical health along with moderate religious practices show significantly greater levels of happiness according to p-value less than 0.01. This study shows that education plays a significant role in improving women's happiness. The results show why policy measures need to focus on improving women's access to education.